Responder Analysis of a Multicomponent Non-Pharmacological Intervention (MAKS) for People With Cognitive Impairment in the German Day-Care Study (DeTaMAKS) - Luttenberger, Katharina; Graessel, Elmar; Behrndt, Elisa-Marie; Özbe, Dominik; Donath, Carolin; Scheel, Jennifer (Frontiers in Psychiatry, 2019)
Background: Multicomponent non-pharmacological therapies have been shown to be effective at reducing cognitive symptoms and slowing deterioration in abilities to perform activities of daily living (ADL) in individuals with cognitive impairment. However, little is known about response rates and predictors of response. Methods: We used data from the German day-care study (DeTaMAKS; De = dementia, Ta = Tagespflege / day-care, MAKS: M = motor stimulation, A = activities of daily living stimulation, K = k/cognitive stimulation, S = social stimulation; n=362), which was based on a cluster-randomized trial of the non-pharmacological, multicomponent, anti-dementive MAKS therapy for people with cognitive impairment in day-care centers. We investigated response (defined according to the as improvement or no deterioration) for three different response criteria: cognition via Mini-Mental State Examination (MMSE) score, activities of daily living (ADL) via Erlangen Test of Activities of Daily Living in Persons with Mild Dementia or Mild Cognitive Impairment (ETAM) score, and behavioral and psychological symptoms of dementia (BPSD) via Neuropsychiatric Inventory Questionnaire (NPI-Q) score. In addition, we calculated the number needed to treat (NTT) and response rates according to net gain analyses. Results: For all three criteria, the response rates were higher in the intervention group than in the control group (Chi2 test: p=0.058 to p=0.003). Compared with non-responders, responders according to cognition had higher ETAM scores (= better ADL abilities) at baseline; responders according to ADL had lower ETAM scores (= poorer ADL abilities) at baseline; responders according to BPSD had higher NPI-Q scores (= more BPSD) at baseline. Classification rates based on these predictors ranged from 60.6% to 68.3%. Discussion: The response rates to the non-pharmacological MAKS therapy were greater than those reported for anti-dementive drugs. There were only a few differences between responders and non-responders. Because of the low classification rates, these variables had only a small impact on response predictions. Therefore, there are no empirically substantiated selection criteria for the application of MAKS therapy in facilities.